2019
DOI: 10.1109/tip.2018.2869696
|View full text |Cite
|
Sign up to set email alerts
|

Triple Verification Network for Generalized Zero-Shot Learning

Abstract: Conventional Zero-shot Learning approaches often suffer from severe performance degradation in the Generalised Zero-shot Learning (GZSL) scenario, i.e. to recognise test images that are from both seen and unseen classes. This paper studies the Class-level Over-fitting (CO) and empirically shows its effects to GZSL. We then address ZSL as a Triple Verification problem and propose a unified optimisation of regression and compatibility functions, i.e. two main streams of existing ZSL approaches. The complementary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 25 publications
0
50
0
Order By: Relevance
“…2. Concretely, besides the baseline results recorded in [25], we also provide the results of four other methods, including TVN [48], VZSL [49], LESAE [13] and LESD [11], among which LESAE and LESD are low rank based methods and most related to ours. From Tab.…”
Section: Results On Zslmentioning
confidence: 99%
“…2. Concretely, besides the baseline results recorded in [25], we also provide the results of four other methods, including TVN [48], VZSL [49], LESAE [13] and LESD [11], among which LESAE and LESD are low rank based methods and most related to ours. From Tab.…”
Section: Results On Zslmentioning
confidence: 99%
“…Recent work showed that generating synthetic samples of unseen classes using GANs or VAEs [48,11,5,57] can substantially improve generalized zero-shot learning . The recent literature considers this generative effort to be orthogonal to modelling, since the two efforts can be combined [29,7,56,15,54]. Here we compare COSMO directly both with the approaches listed above, and with generative approaches fCLSWGAN [48], cycle-(U)WGAN [11], SE-GZSL [5].…”
Section: Compared Methodsmentioning
confidence: 99%
“…Therefore, they propose the new task-Generalised ZSL, which assumes that the search space of the nearest neighbour should be extended to both seen and unseen classes. Recently, Zhang et al in [35] considered GZSL problem as a triple verification problem and a novel optimization of regression and compatibility function is proposed to solve this problem. Subsequently, Xian et al [36] put forward a new standard split of several popular datasets for GZSL testing, and release a benchmark of some recent ZSL methods, which makes the later researchers more convenient and has greatly promoted the development of ZSL.…”
Section: Generalized Zero Shot Learning (Gzsl)mentioning
confidence: 99%